2009
DOI: 10.1007/s00467-008-0989-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibody response to the heptavalent pneumococcal conjugate vaccine in pediatric chronic kidney disease

Abstract: Pneumococcal vaccination has been recommended for immunocompromised children, including patients with chronic kidney disease. We determined pneumococcal immunoglobulin (Ig)G antibodies to serotypes 4, 6B, 9V, 14, 18C, 19F, and 23F before and after 48 pediatric patients with chronic renal failure were administered heptavalent conjugated pneumococcal vaccine. The patients were between 1 and 9 years of age and were separated into a conservative treatment group (Group 1) and a dialysis group (Group 2). The antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…In children on dialysis, a trial with a 7-valent conjugate pneumococcal vaccine demonstrated antibody responses against at least one serotype in all patients at 60 days postvaccination (16). Only 9/24 (37.5%) children on dialysis achieved a 4-fold rise in the concentrations of antibodies to at least five of the seven serotypes over the concentrations at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…In children on dialysis, a trial with a 7-valent conjugate pneumococcal vaccine demonstrated antibody responses against at least one serotype in all patients at 60 days postvaccination (16). Only 9/24 (37.5%) children on dialysis achieved a 4-fold rise in the concentrations of antibodies to at least five of the seven serotypes over the concentrations at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Two small trials studied conjugated pneumococcal vaccines. In the first, more than half of 48 children vaccinated with PCV-7 were non-responders, defined as the absence of a more than four-fold rise in antibody levels for at least five serotypes [14]. In the second, PCV-13 vaccination in 25 adult dialysis patients resulted in a certain antibody response at 2 months that grossly disappeared after 1 year [15].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, HB seroconversion rates and the number of subjects with a protective titer of 10 mIU/mL or greater for antibody against HBsAg (anti-HBs) were lower among children who were taking steroids and also those who were not taking immunosuppressants; this suggested that SSNS was the major cause of their impaired immune responses. Children on dialysis also have a reduced immune response to PCV7 with post-vaccination antibody concentrations only 40% higher than baseline concentrations [60]. Similarly, the MMR vaccine was able to induce adequate antibody responses to all the antigens in only three of ten children on dialysis although antibody responses were observed to measles in eight children, mumps in five children, and rubella in eight children [61].…”
Section: Vaccine Immunogenicitymentioning
confidence: 96%